Biological control of Fusarium graminearum sensu stricto, causal agent of Fusarium head blight of wheat, using formulated antagonists under field conditions in Argentina - Palazzini, Juan Manuel (2016)
Fusarium head blight (FHB) mainly caused by Fusarium graminearum is a devastating disease that causes extensive yield and quality losses to wheat in humid and semi-humid regions of the world. The biocontrol effect of two bacterial strains on FHB incidence, severity and deoxynivalenol (DON) accumulation in wheat was evaluated in field trials during 2010 and 2011 at Marcos Juarez, Córdoba province, Argentina. Bacillus subtilis RC 218 and Brevibacillus sp. RC 263 applied at anthesis period were evaluated through several combinations of cell type, strains, inoculum density (104 and 106cfu/ml) and physiological modification. A significant and consistent biocontrol effect on FHB severity and DON contamination was observed in all the evaluated treatments during both 2010 and 2011 field trials. Reduction in FHB severity ranged 62-76% and 42-58% for 2010 and 2011 field trials, respectively. When evaluating the effect of the combined strains (104+104 and 106+106cfu/ml), a better biocontrol effect was observed in 2010 field trial. After biocontrol treatments, no DON accumulation was observed in wheat heads; meanwhile in control plots an average of 1372μg/kg DON was detected during the two trials. FHB incidence was significantly reduced by biocontrol treatments during the 2010 field trial but not during the 2011 field trial. The results showed the effectiveness of the two formulated biological control agents in reducing both FHB severity and DON accumulation by F. graminearum under semi controlled field conditions.